Looking again at troubled families: parents' perspectives on multiple adversities. (15th April 2015) - Bunting, Lisa; Webb, Mary Anne; Shannon, Rachel
Abstract: The 'Troubled Families' policy and intervention agenda is based on a deficit approach that tends to ignore the role of structural disadvantage in the lives of the families it targets. In an effort to support this rhetoric, both quantitative and qualitative data have been used, and misused, to create a representation of these families, which emphasizes risk and individual blame and minimizes societal factors. This current paper presents findings from an in‐depth qualitative study using a biographical narrative approach to explore parents' experiences of multiple adversities at different times over the life‐course. Key themes relating to the pattern and nature of adversities experienced by participants provide a more nuanced understanding of the lives of families experiencing multiple and complex problems, highlighting how multiple interpretations are often possible within the context of professional intervention. The findings support the increasing call to move away from procedurally driven, risk averse child protection practice towards more relationally based practice, which addresses not only the needs of all family members but recognizes parents as individuals in their own right.